A simulation study on the torrefied biomass gasification. (15th January 2015) - Tapasvi, Dhruv; Kempegowda, Rajesh S.; Tran, Khanh-Quang; Skreiberg, Øyvind; Grønli, Morten
Highlights: Equilibrium model for raw and torrefied biomass with thermodynamic analysis. Experimental pyrolysis yields including tar as inputs to the model. Equivalence ratio had the most pronounced effect on the model outcomes. Torrefied biomass gave higher H2 and CO contents and energy and exergy efficiencies. Torrefaction mass yields affect the gasification process efficiency. Abstract: Many studies have evaluated biomass behavior in a gasification process. Similar studies with torrefied biomass are needed to evaluate the improvements in biomass properties with torrefaction. This forms the basis of this study. A two-stage biomass gasification model is presented by using Aspen Plus as the simulation and modeling tool. The model included the minimization of the Gibbs free energy of the produced gas to achieve chemical equilibrium in the process, constrained by mass and energy balances for the system. Air and steam were used as the oxidizing agent in the process that uses both untreated and torrefied biomass as feedstocks. Three process parameters, equivalence ratio (ER), Gibbs reactor temperature and steam-to-biomass ratio (SBR), were studied. 27 cases were included in the analysis by operating the system below the carbon deposition boundary with all carbon in gaseous form in the product gas. Product gas composition in the form of hydrogen (H2 ), carbon monoxide (CO), carbon dioxide (CO2 ), methane (CH4 ) and nitrogen (N2 ) was analyzed together with cold gas energy and exergy efficiencies for all the cases. Overall, mole fractions of H2, CO, CO2 and N2 were between 0.23–0.40, 0.22–0.42, 0.01–0.09 and 0.14–0.36 for torrefied wood and 0.21–0.40, 0.17–0.34, 0.03–0.09 and 0.15–0.37 for untreated wood, respectively. Similarly, cold gas energy and exergy efficiencies were between 76.1–97.9% and 68.3–85.8% for torrefied wood and 67.9–91.0% and 60.7–79.4% for untreated wood, respectively. Torrefied biomass has higher H2 and CO contents in the product gas and higher energy and exergy efficiencies than the untreated biomass. Overall efficiencies of an integrated torrefaction–gasification process depend on the mass yields of the torrefaction process. Results from this study were validated using a C–H–O ternary diagram and with results from other similar studies.